Gênero gramatical e biológico de substantivos do português brasileiro: uma análise baseada em corpus - Leão, Daniel de Almeida (2016)
This study has as its main goal to investigate the relation between the grammatical system of gender classification for the nouns of the Portuguese language in Brazil and the biological gender of their referents from the perspective of language as a probabilistic system (Halliday, 1991, 1993). More specifically, the investigation extracted the frequencies for the grammatical gender of the nouns (masculine and/or feminine) for the Portuguese language in Brazil and the relation between the grammatical gender and the biological sex of the nouns. For such, this study has as its basis the Corpus Linguistics, a theoretical-scientific methodology which sees the language as a probabilistic system, through the observation of empirical data (Berber Sardinha, 2004). Although the grammatical gender is an aspect of the language approached throughout the grammars of the Portuguese language and its study constantly discussed among scholars and researchers of the field, the great majority of these studies have as basis a traditional perspective of the language, brought by the use of norms (Bechara, 2013). This means that, possibly, there is no other study about this subject which is based on the language in use, in a probabilistic approach (Halliday, 1991, 1993), following the principles of Corpus Linguistics (Berber Sardinha, 2004). In order to accomplish this goal, this work was executed as the following: (i) all the nouns of a corpus (The Brazilian Corpus of Register Variation – CBVR) were extracted; (ii) the nouns were transferred to a database in which they could be classified; (iii) the nouns were classified manually in respect to their grammatical gender and biological gender, following the criteria described in this work’s methodology; (iv) after classifying the nouns, they were accounted according to each of the categories described in the methodology, (v) after that, for each research question, the frequencies were extracted and the probabilities were calculated and; (vi) the research questions were answered based on how the frequencies and probabilities had been revealed. In bringing up the results, it is expected that this research has been able to contribute for offering a new perspective about this subject, one that takes into account the current Portuguese language in Brazil for the 21st century. It is also expected that the methodology designed for the execution of this study could be adapted and applied to several other studies of similar goals, bringing new perspectives for other aspects of the language